Relationship Between Outdoor Adventure Education Programs and Environmental Sustainability Behaviors Among Youths in Ondo State, Nigeria - Bola D. Ojo; Folusade C. Arowosafe (European Scientific Journal, ESJ, 2026)
This study examined the relationship between outdoor adventure education (OAE) programs and environmental sustainability behaviors among 360 youths in Ondo State, Nigeria (63.6% male, 36.4% female; 70.5% aged 18-34; Yoruba, with low-to-middle income and secondary/higher education). Using a correlational survey design and self-report questionnaire data collection across amusement parks, recreation, sports, and tourism, the study revealed a significant positive relationship between participation in these programs and sustainability behaviors among youths. Mean ratings across contexts ranged from 2.76 to 3.04, indicating consistent agreement. Statistical analysis further showed significant correlations between OAE context: amusement park (r = .660), recreation (r = .515), sports (r=.832), tourism (r=.703), and environmental sustainability behaviors among youths (p < .05). Regression analysis showed these contexts jointly explain 30.2% of variance in sustainability behaviors (R=.302, F=38.85, p < .001). The findings recommend integrating environmental education into youth programs across these sectors.